Assessment of tolerance of cotton genotypes to jassids - Mutaviri, Lovemore; Mubvekeri, Washington (Open Science Journal, 2024)
Tolerance of cotton genotypes to jassids attacks should be one of the on-going research programmes that Cotton Research Institute (CRI) should continue to carry on. This is because pests have a tendency of developing resistance to the use of insecticides which has become the most common and relied upon form of pest control in Zimbabwe’s farmers. This can be done by fusion of tolerant traits which can be both genetic and morphological. Among the morphological traits are the openness, hairiness and small leaves. Openness reduces the density of leaf foliage thereby making difficult the moving of jassids, especially the nymphs that cannot fly, from one leaf to the next. Hairiness makes the jassid uncomfortable getting into contact with the hairy cotton due to their soft body tissue. Other traits like nectariless, gossypol content, reduced pubescence, tannins and trichome densities are genetic traits that increases varietal resistance to jassids attack on cotton. Fourteen medium staple genotypes namely 562-00-9, 564-00-6, 566-99-23, 651-01-1, 665-01-3, 666-01-2, 668-01-2, 816-01-1, 833-01-3, 931-05-9, 937-05-4, 97-05-1, LV96-05-8, SO-99-9 and two released varieties CRI MS1(check) and Delmac (check) were evaluated for their tolerance to jassids population and damage for three seasons from 2018-19 up to 2020-21 at Chibuwe, CRI, Muzarabani, Shamva and Umguza. The experimental design used was a Square lattice (partially balanced and randomized blocks) replicated three times. Treatments 97-05-1, 937-05-4, 562-00-9 and 666-01-2 were the best performing genotypes in terms of jassid resistance in most sites and seasons.